Quality of Antibiotic Prescribing for Respiratory Tract Disease in Primary Healthcare Centers in the District of Tegal, Central Java, Indonesia - Farida Fakhrunnisa; Retnosari Andrajati; Maksum Radji (Indonesian Journal of Clinical Pharmacy, 2020)
The prescription of antibiotics for diagnosed upper respiratory tract infections (URTIs) is frequently practiced. Furthermore, inappropriate use has been implicated in numerous problems, including the onset of resistance. This study is, therefore, aimed to evaluate the antibiotic prescribing quality for respiratory tract disease diagnosed at the outpatients of primary healthcare centers in Tegal District, Central Java, Indonesia. In addition, cross-sectional evaluation was employed, using data obtained within the period of June–August, 2018 in six locations, and subsequently subjected to qualitative analysis. The prescribing quality was evaluated by comparing the drug selected, dosage, frequency, and duration of administration stated in the prescriptions, with the terms in the Clinical Practice Guidelines for Primary Healthcare Facilities, 2014. A total of 1453 samples were selected through purposive sampling, where 632 were diagnosed with respiratory tract diseases, with common cold as the most frequent diagnosis (87.2%). In addition, exactly 621 (98.3%) failed to fulfill the rational antibiotic prescribing criteria, evidenced by irrational drug selection (22.0%), dosage (9.5%), frequency (1.7%), and duration of administration (65.0%). The physicians tend to comply more with the national treatment guidelines (OR: 1.828, 95%CI: 0.486–6.874, p-value 0.365), and the less experience of prescribers (<12 years of service) was identified as a negative contributing factor (OR: 0.536, 95%CI: 0.143–2.016, p-value 0.349). Furthermore, irrational prescription was observed in a much larger proportion, influenced by the prescribers’ qualification and experience. This association is currently not significant, due to deficiency of influencing samples.Keywords: Antibiotic, appropriateness prescribing, national treatment guidelines, qualification prescribers, rationality Kualitas Peresepan Antibiotik pada Penyakit Saluran Pernafasan di Beberapa Puskesmas di Kabupaten Tegal, Jawa Tengah, IndonesiaAbstrakPeresepan antibiotik untuk diagnosis infeksi saluran pernafasan atas sering dilakukan. Peresepan antibiotik yang tidak tepat dapat menyebabkan banyak masalah, salah satunya resistensi antibiotik. Tujuan dari penelitian ini adalah mengevaluasi kualitas peresepan antibiotik pada diagnosis penyakit saluran pernafasan pasien rawat jalan di Puskesmas Kabupaten Tegal, Jawa Tengah, Indonesia. Penelitian potong lintang menggunakan data peresepan pasien rawat jalan periode Juni–Agustus 2018 di enam puskesmas di Kabupaten Tegal. Resep dengan diagnosis penyakit saluran pernafasan digunakan untuk analisis kualitatif. Kualitas peresepan dinilai dengan membandingkan pemilihan obat, dosis pemberian, frekuensi pemberian dan durasi pemberian antara yang tertulis pada resep dengan Panduan Praktik Klinis Fasilitas Kesehatan Primer 2014. Sebanyak 1453 resep diambil secara purposive sampling, 632 resep di antaranya dengan diagnosis penyakit saluran pernafasan. Diagnosis yang paling sering yaitu salesma (87,2%). Sebanyak 621 (98,3%) resep tidak memenuhi kriteria peresepan antibiotik yang rasional, meliputi ketidakrasionalan pemilihan antibiotik (22,0%), dosis pemberian (9,5%), frekuensi penggunaan (1,7%), dan durasi pemberian (65,0%). Peresepan antibiotik oleh dokter lebih sesuai dengan panduan pengobatan nasional (OR 1,828, 95% CI: 0,486–6,874, p-value 0,365). Pengalaman penulis resep yang lebih singkat (<12 tahun) juga menjadi faktor persepan tidak rasional (OR 0,536, 95% CI: 0,143–2,016, p-value 0,349). Sebagian besar peresepan antibiotik pada penyakit saluran pernafasan tidak rasional. Baik kualifikasi maupun pengalaman penulis resep pada penelitian ini memiliki memengaruhi rasionalitas resep, meskipun tidak (belum) signifikan karena kurangnya sampel terhadap kerasionalan.Kata kunci: Antibiotik, kerasionalan, kesesuaian peresepan, kualifikasi penulis resep, panduan pengobatan nasional